Creative cities : a case study on Lisbon - Helm, Irene (2016)
The city today is progressively conceptualized by using terms, such as Creative Cities or Creative Class and stressing the importance of Creativity. Lisbon is here in focus, considering the implementation of the ideas behind the Creative City concept by Richard Florida and Charles Landry, as well as the critical responses from the cultural sector. “Creativity” in this context refers to the elaboration of new ideas and to the application of these ideas to produce original works of art and cultural products, and technological innovations. Furthermore does this thesis reveal the impact of changes made socially and physically based on examples in the metropolitan area of Lisbon. Moreover is the focus on the work of cognitive-cultural employees in the Creative City and beyond, because the idea of creativity in the workplace offers opportunities for urban development and the personal development of urban inhabitants. This will be developed through a critique of the literature and some illustrative examples of people with creative occupations or by highlighting different location in Lisbon. The focus to change urban spaces lays in a deeper understanding of how “creativity” is constructed and performed in specific urban contexts in order to be sustainable.